Pengaruh Disiplin, Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Karyawan pada Reny Swalayanku Surabaya - Karina Eka Febriyanti; Diana Juni Mulyati; Ayun Maduwinarti (Politeknik Kampar, 2024)
Employee performance in a company is very important to maintain smooth operations and customer satisfaction. Every year employee performance is required to be more developed even though sometimes a company experiences a decline in performance, to achieve maximum employee performance according to what the company wants in achieving its goals. Therefore, employee performance is the main key to the success of a company. Increasing overall employee performance in a company will increase the smoothness of the work process and a smooth work process will also make it easier to achieve the company's goals. This research takes the object of Reny Swalayan-Ku Surabaya. In this research, 4 variables were taken, namely discipline, organizational culture, work motivation and employee performance. This research uses quantitative research methods. The sample used in this research was all 77 employees of Reny Swalayan-ku. The data collection method uses a questionnaire. The data analysis techniques used in this research are the classical assumption test, multiple linear regression test, and hypothesis testing. The results of this research show that first, discipline partially has a significant effect on employee performance. Second, partially organizational culture has a significant effect on employee performance. Third, partially work motivation has a significant effect on employee performance. Then, the results of the simultaneous test show that the Fcount value is 29.362 > Ftable is 2.730 at a significance level of 0.000, so it can be concluded that discipline, organizational culture and work motivation together have a significant influence on employee performance.